Local action planning and cost–benefit analysis of climate adaptation strategies in climate-vulnerable value chains in Nampula and Zambezia, Mozambique - Mundia, Carolyne; Jalango, Dorcas; Binge, Brenda; Chilambe, Pedro (2025)
Climate change poses growing risks to agricultural productivity and rural livelihoods in Mozambique, particularly in highly vulnerable provinces such as Nampula and Zambezia, where increasing droughts, floods, and cyclones disrupt farming systems, value chains, and food security. While national and sectoral adaptation strategies are well articulated, translating these priorities into effective local action remains a critical challenge. This implementation guideline addresses this gap by providing a practical, step-by-step framework for operationalising climate adaptation at the local level. Targeted at district planners, extension officers, non-governmental organisations, farmer organisations, and other stakeholders, the guideline builds on existing climate-smart agriculture frameworks and empirical evidence from climate vulnerability assessments across key agricultural value chains. It supports the development of localized action plans with clear timelines, stakeholder roles, investment requirements, and short-, medium-, and long-term activities for prioritized adaptation measures. The guideline adopts a structured, results-oriented approach that links risk identification, adaptation prioritization, and implementation planning. Importantly, it also integrates economic reasoning by validating selected high-impact interventions through cost–benefit analysis, thereby providing decision-makers with an evidence-based foundation for allocating resources and scaling adaptation investments that are both climate-resilient and economically viable.